1992
DOI: 10.1002/cjce.5450700423
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of solutions in the optimization of a bifunctional catalyst blend in a tubular reactor

Abstract: The reaction scheme for the isomerization and hydrogenation of methylcyclopentane using bifunctional catalyst is considered in a tubular reactor. The aim is to maximize the concentration of benzene at the outlet of the reactor by choosing the optimal blend of the catalyst along the reactor. When the problem was attempted by nonlinear programming employing sequential quadratic programming, twenty‐five local optima were obtained from 100 random starting conditions. By using iterative dynamic programming in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 13 publications
0
33
0
2
Order By: Relevance
“…A 6 A 7 A ~X 3~ k 8 10 2 k 7 k 3 9 1: ' k, :,1:, Al ~ This problem has been studied by Luus et al (1992), Bojkov and Luus (1993), and Luus and Bojkov (1994). Even though this example is relatively small (7 states and 1 control), it has been shown to exhibit a very large number of loeal minima.…”
Section: Datamentioning
confidence: 99%
“…A 6 A 7 A ~X 3~ k 8 10 2 k 7 k 3 9 1: ' k, :,1:, Al ~ This problem has been studied by Luus et al (1992), Bojkov and Luus (1993), and Luus and Bojkov (1994). Even though this example is relatively small (7 states and 1 control), it has been shown to exhibit a very large number of loeal minima.…”
Section: Datamentioning
confidence: 99%
“…Let us now consider the optimization of a bifunctional catalyst in converting methylcyclopentane to benzene in a tubular reactor. It is extremely interesting to investigate this system because of its multitude of local optima and the inability of nonlinear programming to obtain the global optimum, even when using 100 different starting points as discussed by Luus et al (1992). Recently, Storey (1992) showed that for this system Simulated Annealing, Modified Controlled Random Search and Multilevel Single Linkage also were unable to yield the global optimum.…”
Section: Blendmentioning
confidence: 99%
“…n the investigation of design possibilities of engineering I systems, one is frequently confronted with problems of determining the optimal control of systems described by a large number of nonlinear differential equations. Although, there are numerous numerical methods that can be used, in many situations it is difficult to foresee the existence of local optima, thus rendering the search for the global optimum solution extremely difficult, as shown by Luus et al (1992) and Storey (1992). Even if one uses an optimization procedure that has been reliable for many problems, it is prudent to cross-check the solution of a new problem by using some different optimization method.…”
mentioning
confidence: 99%
“…The nonlinearity can result in a highly nonconvex problem exhibiting many suboptimal local solutions. It is known that even small-scale dynamic systems can exhibit multiple suboptimal local solutions [12][13][14]. Unfortunately, a derivative-based optimization method can become trapped in any of these, which can lead to a suboptimal operation and loss of profit.…”
Section: Introductionmentioning
confidence: 99%